Where East looks West : success in English in Goa and on the Konkan Coast - Kurzon, Dennis (Multilingual Matters S., 2004)
The aim of this text to explain the constant success in the TOEFL (Test of English as a Foreign Language) of speakers of the Indian language, Konkani, who live in Goa and to the south of Goa.